The Effect of Hypnotherapy on Anticipatory Nausea in Head and Neck Cancer Patients Undergoing Chemotherapy - Hamdani, Dadi; Prasetyo, Awal; Anggorowati, Anggorowati (Nurse Media Journal of Nursing, 2020)
Background: One of the chemotherapy side effects on head and neck cancer patients is anticipatory nausea. However, the anticipatory nausea problem has not been properly resolved. Nausea might be psychologically reduced by hypnotherapy. There only have been very few studies conducted to examine the effects of hypnotherapy in alleviating anticipatory nausea.Purpose: This study aimed to determine the effect of hypnotherapy using Hanung induction technique on anticipatory nausea in head and neck cancer patients undergoing chemotherapy.Methods: This research employed a pre-post test of quasi-experiment with control group design. Consecutive sampling technique was used to obtain 64 subjects who met inclusion and exclusion criteria and were equally divided into the intervention and control groups. Hypnotherapy as the intervention was carried out in two sessions, each of which lasted for 20 minutes, with a week distance between sessions. The data were collected using a visual analog scale (VAS), which was used twice to measure anticipatory nausea and analyzed using the paired and independent-sample t-test.Result: The results showed that the mean score of anticipatory nausea in the intervention group reduced from 7.6±1.4 to 2.3 ±1.2 after hypnotherapy, while the mean in the control group increased from 6.4±1.6 to 6.7±1.4. There was a significant difference in the score of anticipatory nausea after the implementation of hypnotherapy between the intervention and the control group (p<0.001).Conclusion: The study concluded that hypnotherapy is effective in reducing the intensity of anticipatory nausea in head and neck cancer patients undergoing chemotherapy. Therefore, hypnotherapy can be applied by oncology nurses as an intervention in treating anticipatory nausea.